Persepsi Masyarakat terhadap Kesehatan dan Kebersihan Air Minum Isi Ulang di Kabupaten Merauke - Ronald Ronald; Pricilya Margaretha Warwuru (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
With the increasing rate of human growth, the need for clean water is also increasing. The increase in population needs to be balanced with an increase in the amount of quality water. Good water quality must also be considered in fulfilling daily needs because the quality of clean water will affect health. The percentage of households with access to proper drinking water in Indonesia is 91.05%. Papua Province is below the national standard, namely 65.39%. Research conducted in 2018 only 68.2% of drinking water depots in Merauke were free of coliforms. The purpose of this study is to describe the perceptions of the Merauke people about the cleanliness and health of the refilled drinking water they consume. This research was conducted in Merauke district, Merauke district. This type of research is quantitative research with a descriptive design with an accidental random sampling technique. Data were analyzed and presented descriptively. The results showed that the public's perception of the cleanliness and health of refilled drinking water was not very good. So it is necessary to carry out further studies and interventions. It is necessary to conduct further studies regarding the quality of refilled drinking water in Merauke by reviewing various health aspects. There has never been any research on water quality testing in Merauke using three parameters, namely physics, chemistry, and biology. Interventions and follow-up research can contribute information on the quality of refilled drinking water consumed by the public.